2012
DOI: 10.1262/jrd.11-122t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cortisol on Pregnancy Rate and Corpus Luteum Function in Heifers: An <i>In Vivo</i> Study

Abstract: Abstract. To determine whether glucocorticoids affect the function of the bovine corpus luteum (CL) during the estrous cycle and early pregnancy, we examined the effects of exogenous cortisol or reduced endogenous cortisol on the secretion of progesterone (P4) and on pregnancy rate. In preliminary experiments, doses of cortisol and metyrapone (an inhibitor of cortisol synthesis) were established (n=33). Cortisol in effective doses of 10 mg blocked tumor necrosis factor-induced prostaglandin F 2α secretion as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…These results indicate that the down-regulation of progesterone may be associated with the function of CL. It has been reported that ACTH or cortisol can inhibit the basal secretion of LH and the preovulatory LH surge by reducing GnRH release (38,39). The alteration of LH levels may influence progesterone secretion in CL.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the down-regulation of progesterone may be associated with the function of CL. It has been reported that ACTH or cortisol can inhibit the basal secretion of LH and the preovulatory LH surge by reducing GnRH release (38,39). The alteration of LH levels may influence progesterone secretion in CL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we suggested that an active GC, cortisol (Cr), affects pregnancy rate and CL function in cattle [8]. In addition, Cr suppresses basal and tumor necrosis factor-α-stimulated PGF production in bovine endometrial stromal cells but not in the epithelial cells [9].…”
mentioning
confidence: 99%
“…2007). Furthermore, treatment of metyrapone, an inhibitor of HSD11B1, to reduce the local availability of Cr converted from cortisone in the bovine reproductive tract at the late luteal stage prolonged the luteal phase in cows (Duong et al. 2011a).…”
Section: Discussionmentioning
confidence: 99%